Investigation of the effects of turbine and pipe design on pico-hydropower generator system performance in flowing water - Nurhafizah, Abu Talip Yusof; Haziq Irfan, Hamdan; Lee, Lai Kok; Yasmin, Abdul Wahab; Mohamad Shaiful, Abdul Karim; Ahmad Syahiman, Mohd Shah (Institution of Engineering and Technology, 2022)
Pico-hydropower (PHP) is a small hydroelectric power plant system that can be used in rural areas to generate electricity. The purpose of this research is to investigate the impact of turbine and pipe design on the performance of a PHP generator system in flowing water. This is owing to the objective of developing a PHP generator system that can easily be installed and operated at an affordable rate to generate electricity for daily usage. Fabrication of the turbine and pipe is done with a 3D printer. The performance of PHP based on the turbine and nozzle pipe design is then assessed by determining the output in terms of voltage and power. The potential energy of the water stream will strike the turbine, which will rotate the generator, converting mechanical energy into electricity. The preliminary investigation results revealed that suitable numbers of blades, that is, 8 blades of a Pelton turbine, can generate up to 5.89 V of voltage as compared to 16 blades of a Pelton turbine, which produces 5.35 V of voltage output. The highest power produced was 530.1 mW which was given by 15o gradually reduced nozzle pipe type that was implemented together with an 8-blade Pelton turbine.